Mental models of the concept of carbon cycle via self-generated visualisation among matriculation college science students - Abd. Rahman, Roszelina; Salih, Maria (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Among the objectives of this study was to identify and explain matriculation college science student’s mental models generated from self-visualisation of the concept of the carbon cycle. Five students were purposively sampled and the study was carried out in a naturalistic setting qualitative approach. Data was collected through a visualisation task and followed by interviews. The constant comparative qualitative technique was used to analyse differences and similarities that led to patterns in their mental visualisation. Findings showed two patterns of mental models; namely pictorial and graphical mental models. These students visualised themselves from their own experiences and made relationships to their prior and new knowledge. Keyword selection coincided with the concept used for the generation of visualisation. This study expects to help formulate a framework for teaching and learning to guide students to generate a significant mental visualisation of abstract science concepts.